The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3892/or.2011.1556
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of murine melanoma growth by a vaccine of attenuated Salmonella carrying heat shock protein 70 and Herpes simplex virus-thymidine kinase genes

Abstract: Abstract. Attenuated Salmonella can invade tumor cells and acts as a eukaryotic expression vector for gene propagation. We constructed a bi-gene, eukaryotic co-expression DNA vaccine of Mycobacterium tuberculosis heat shock protein 70 (mtHSP70) and Herpes simplex virus-thymidine kinase (HSV-tk) and used attenuated Salmonella as a vector to treat murine melanoma. In vitro, recombinant Salmonella can carry plasmid stably and can invade into the cytoplasm of B16 tumor cells expressing the protein of the mtHSP70/H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A similar study using Bifidobacterium infantis as the HSVtk-expression vector showed similar anti-tumor activity in a rat model of bladder cancer [ 113 ]. Moreover, a co-expression, bi-gene GDPT system was investigated by Zeng et al , 2012 [ 111 ]. Melanoma-bearing mice were administered with S. Typhimurium co-expressing Mycobacterium tuberculosis heat shock protein 70 (mtHS70) and HSVtk, and upon administering GCV, increased IFN-γ levels within tumor tissue and marked tumor growth retardation was observed.…”
Section: Live-attenuated Bacterial Vectors For Cancer Treatmentmentioning
confidence: 99%
“…A similar study using Bifidobacterium infantis as the HSVtk-expression vector showed similar anti-tumor activity in a rat model of bladder cancer [ 113 ]. Moreover, a co-expression, bi-gene GDPT system was investigated by Zeng et al , 2012 [ 111 ]. Melanoma-bearing mice were administered with S. Typhimurium co-expressing Mycobacterium tuberculosis heat shock protein 70 (mtHS70) and HSVtk, and upon administering GCV, increased IFN-γ levels within tumor tissue and marked tumor growth retardation was observed.…”
Section: Live-attenuated Bacterial Vectors For Cancer Treatmentmentioning
confidence: 99%
“… 91 Immunostimulating molecules such as glycoprotein (gp100) or heat shock protein ( M. tuberculosis heat shock protein 70) elicit host-derived protective immunity to suppress tumor development. 92 93 …”
Section: Strategies For S Typhimurium -Mediated Cmentioning
confidence: 99%